ANALISIS SINYAL SUARA JANTUNG DENGAN MENGGUNAKAN ANALISIS SPEKTRUM - Daso, Fransiscus; Irawan, Jusak; Puspasari, Ira (Journal of Control and Network Systems, 2015)
The use of graphs to analyze heart sound signals quite difficult, because the cardiac signals are retrieved and displayed into a graph requires special skills to be able to read and analyze the cardiac signal. Therefore, the authors took the initiative to create an application that can transform the heart sound signal from the time domain into the frequency domain for analysis needs.The process of transformation of heart sound signals using Fast Fourier Transform (FFT).Based on the test results showed the transformation of the heart signal from the time domain to the frequency domain in the experiment with six different cases is particularly evident in the Peak or peak frequency and maximum frequency. Abnormalities of the heart sound signal with voice disorders at low frequencies produces a frequency domain representation of the graph with a small hill in the low frequencies.Â